Penerapan Distinction Principle Dalam Perundang-Undangan di Indonesia - Prasetiawan, Eno; Hastuti, Lina (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 9 No 2 (2020), 2020)
The ratification of the 1949 Geneva Convention implies that Indonesia must obey and implement international humanitarian law, specifically the distinction principles. One of the distinction principle relates to the separation of civilian objects and military objects, where attacks are only passed on to military objects. civilian objects and military objects in Indonesia are practically not separated and close together. This has the potential to become a threat if it does not follow the rules in international humanitarian law. The purpose of this study is to find out the importance of applying the distinction principle regarding civil objects and military objects in legislation in Indonesia. This writing uses a normative legal research method, the approach is carried out through a legislative approach and a conceptual approach. The results of the study indicate that the separation of civilian and military objects is a preventive effort in protecting civilians and civilian objects in the event of war or armed conflict. Although it has been a party to the 1949 Geneva convention, the application of the principle of differentiation has not yet been fully implemented by Indonesia, there are no specific regulations regarding the separation of civilian and military objects in its national legislation. Ratifikasi Konvensi Jenewa 1949 berimplikasi adanya kewajiban Indonesia untuk mematuhi dan melaksanakan hukum humaniter internasional, khsusnya prinsip pembedaan. Salah satu prinsip pembedaan terkait pemisahan objek sipil dan objek militer, di mana ketika berperang serangan-serangan hanya dibenarkan ke objek-objek militer saja. Objek sipil dan objek militer di Indonesia secara praktik tidak dipisahkan atau berdekatan. Ini berpotensi menjadi ancaman khususnya bagi keselamatan penduduk sipil apabila tidak mengikuti aturan di dalam hukum humaniter internasional. Tujuan penelitian ini adalah untuk mengetahui pentingnya penerapan distinction principle terkait objek sipil dan objek militer dalam perundang-undangan di Indonesia. Penulisan ini menggunakan metode penelitian hukum normatif, dengan melakukan pendekatan melalui perundang-undangan dan pendekatan konseptual. Hasil penelitian menunjukkan bahwa Pemisahan objek sipil dan militer merupakan upaya preventif dalam melindungi penduduk sipil dan objek-objek sipil jika terjadi perang atau konflik bersenjata. Meskipun telah menjadi pihak dalam konvensi jenewa 1949, penerapan prinsip pembedaan belum sepenuhnya dilaksanakan oleh Indonesia, belum ada peraturan khusus terkait pemisahan objek sipil dan militer dalam legislasi nasionalnya.